Xylan degradation by the human gut Bacteroides xylanisolvens XB1AT involves two distinct gene clusters that are linked at the transcriptional level. (December 2016) - Despres, Jordane; Forano, Evelyne; Lepercq, Pascale; Comtet-Marre, Sophie; Jubelin, Gregory; Chambon, Christophe; Yeoman, Carl; Berg Miller, Margaret; Fields, Christopher; Martens, Eric; Terrapon, Nicolas; Henrissat, Bernard; et al.
Abstract Background Plant cell wall (PCW) polysaccharides and especially xylans constitute an important part of human diet. Xylans are not degraded by human digestive enzymes in the upper digestive tract and therefore reach the colon where they are subjected to extensive degradation by some members of the symbiotic microbiota. Xylanolytic bacteria are the first degraders of these complex polysaccharides and they release breakdown products that can have beneficial effects on human health. In order to understand better how these bacteria metabolize xylans in the colon, this study was undertaken to investigate xylan breakdown by the prominent human gut symbiontBacteroides xylanisolvens XB1AT . Results Transcriptomic analyses ofB. xylanisolvens XB1AT grown on insoluble oat-spelt xylan (OSX) at mid- and late-log phases highlighted genes in a polysaccharide utilization locus (PUL), hereafter called PUL 43, and genes in a fragmentary remnant of another PUL, hereafter referred to as rPUL 70, which were highly overexpressed on OSX relative to glucose. Proteomic analyses supported the up-regulation of several genes belonging to PUL 43 and showed the important over-production of a CBM4-containing GH10 endo-xylanase. We also show that PUL 43 is organized in two operons and that the knockout of the PUL 43 sensor/regulator HTCS gene blocked the growth of the mutant on insoluble OSX and soluble wheat arabinoxylan (WAX). The mutation not only repressed gene expression in the PUL 43 operons but also repressed gene expression in rPUL 70. Conclusion This study shows that xylan degradation byB. xylanisolvens XB1AT is orchestrated by one PUL and one PUL remnant that are linked at the transcriptional level. Coupled to studies on other xylanolyticBacteroides species, our data emphasize the importance of one peculiar CBM4-containing GH10 endo-xylanase in xylan breakdown and that this modular enzyme may be used as a functional marker of xylan degradation in the human gut. Our results also suggest thatB. xylanisolvens XB1AT has specialized in the degradation of xylans of low complexity. This functional feature may provide a niche to all xylanolytic bacteria harboring similar PULs. Further functional and ecological studies on fibrolyticBacteroides species are needed to better understand their role in dietary fiber degradation and their impact on intestinal health.